2021
DOI: 10.1051/0004-6361/202038896
|View full text |Cite
|
Sign up to set email alerts
|

LOFAR Deep Fields: probing a broader population of polarized radio galaxies in ELAIS-N1

Abstract: We present deep polarimetric observations of the European Large Area ISO Survey-North 1 (ELAIS-N1) field using the Low Frequency Array (LOFAR) at 114.9-177.4 MHz. The ELAIS-N1 field is part of the LOFAR Two-metre Sky Survey deep fields data release I. For six eight-hour observing epochs, we align the polarization angles and stack the 20-resolution Stokes Q, U-parameter data cubes. This produces a 16 deg 2 image with 1σ QU sensitivity of 26 µJy beam −1 in the central area. In this paper, we demonstrate the feas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…This facilitates a range of science goals aimed at investigating magnetic fields (e.g. Heald et al 2020;O'Sullivan et al 2020;Herrera Ruiz et al 2021;Hutschenreuter et al 2022). Despite the high Galactic latitudes of the observations (b ∼ −33 • & 70 • ), this catalogue contains over 30 known pulsars, over 50% of which are MSPs (O'Sullivan et al, in prep.).…”
Section: Introductionmentioning
confidence: 99%
“…This facilitates a range of science goals aimed at investigating magnetic fields (e.g. Heald et al 2020;O'Sullivan et al 2020;Herrera Ruiz et al 2021;Hutschenreuter et al 2022). Despite the high Galactic latitudes of the observations (b ∼ −33 • & 70 • ), this catalogue contains over 30 known pulsars, over 50% of which are MSPs (O'Sullivan et al, in prep.).…”
Section: Introductionmentioning
confidence: 99%
“…However, thanks to improving instruments and observational techniques we have started to detect polarised low-frequency emission as well [77]. Furthermore, there have been attempts to apply the stacking technique to polarised low-frequency emission [29,78].…”
Section: Measuring Magnetic Fields and Cosmic Raysmentioning
confidence: 99%
“…We used the catalogue of the polarised sources provided by Herrera Ruiz et al (2021) to check how many of them we detect in our final stacked Faraday cube. The purpose of this comparison is only to verify our stacking method on very low-resolution data.…”
Section: Cross-checking the Detection Of The Radio Sourcesmentioning
confidence: 99%
“…Herrera Ruiz et al (2021) did an initial analysis of polarised radio sources in the LoTSS Deep Fields using six eight-hour observations of the ELAIS-N1 field. They used low-resolution (20 ) polarimetric images (Sabater et al 2021) and successfully demonstrated the feasibility of stacking LOFAR data.…”
Section: Introductionmentioning
confidence: 99%